Interpretacje motywu kruka z opowiadania o Potopie - Marczewski, Antoni (Verbum Vitae, 2017)
The motif of the raven, which appears in the Biblical flood narrative (Gen 8:7), has no widely embraced, straightforward interpretation. While the article does present some solutions proposed by contemporary exegetes, it concentrates instead on the passage’s Wirkungsgeschichte, i.e. the manner in which this text inspired ancient translations, Jewish Midrashic literature, and Christian homiletics.